2013
DOI: 10.1017/s0016672313000037
|View full text |Cite
|
Sign up to set email alerts
|

Association of intronic repetition of SLC26A4 gene with Hashimoto thyroiditis disease

Abstract: Intronic microsatellites repeats were implicated in the pathogenic mechanisms of several diseases. SLC26A4 gene, involved in the genetic susceptibility of autoimmune thyroid disease (AITD), harbours large non-coding introns. Using the tandem repeat finder (TRF) Software, two new polymorphic microsatellite markers, rs59736472 and rs57250751, located at introns 10 and 20, respectively, were identified. A case-control design including 308 patients affected with AITD (146 GD, 90 HT and 72 PIM) and 212 unmatched he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
(29 reference statements)
0
3
0
1
Order By: Relevance
“…Moreover, some of these repeats can have an effect on the phenotype and the length of microsatellites is particularly important in this aspect (Sjakste et al, 2013). Long alleles are associated to high predisposition to pathologies (Belguith-Maalej et al, 2013). In relation to coat color, a recent study revealed the presence of a large intronic insertion in Tyrosinase Associated Protein 1 ( TYRP1 ) of the American Mink that alters the splicing of the gene and produces the American Palomino phenotype (Cirera et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some of these repeats can have an effect on the phenotype and the length of microsatellites is particularly important in this aspect (Sjakste et al, 2013). Long alleles are associated to high predisposition to pathologies (Belguith-Maalej et al, 2013). In relation to coat color, a recent study revealed the presence of a large intronic insertion in Tyrosinase Associated Protein 1 ( TYRP1 ) of the American Mink that alters the splicing of the gene and produces the American Palomino phenotype (Cirera et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The intronic microsatellites repeats are implicated in the pathogenic mechanisms of several autoimmune diseases. The SLC26A4 gene, involved in the genetic susceptibility of autoimmune thyroid disease, harbours two microsatellites in the introns 10 and 20; longer alleles of these markers appear to be associated with Hashimoto thyroiditis [106].…”
Section: Dna Secondary Structurementioning
confidence: 99%
“…Intronic microsatellites repeats are implicated in the pathogenic mechanisms of several autoimmune diseases. The SLC26A4 gene, involved in the genetic susceptibility of autoimmune thyroid disease, harbors 2 microsatellites in introns 10 and 20, and longer alleles of these markers appear to be associated with Hashimoto thyroiditis (58). The intronic rs63749745 marker of the 14q13 locus has manifested a high level of association with Graves' disease (59), and rs71928782, rs5807818, rs71444202, and rs345802276 have been found to be in association with juvenile idiopathic arthritis in children (60).…”
Section: Introductionmentioning
confidence: 99%